Peran Tiktok Sebagai Media Komunikasi Politik Bagi Generasi Milenial (Studi Kasus Pada Karyawan Duta Lampung Tahun 2024) - Albarzand, Ahmad Faridh; Choiriyati, Sri; Azizah, Meylin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the role of TikTok as a political communication medium for the millennial generation. With the development of technology and social media, TikTok has emerged as a platform that is not only used for entertainment, but also as a means to convey political messages. Through a qualitative approach, this research collects data from interviews and analysis of video content related to political issues on TikTok. The findings show that TikTok has great potential to influence the political views of the millennial generation, especially through a creative and accessible format. In addition, user interaction on this platform creates space for more dynamic discussion and dissemination of political information. This research provides insight into how social media, especially TikTok, can function as a tool for political mobilization and strengthening the active participation of the millennial generation in the political process. The conclusions of this research underscore the importance of understanding the dynamics of political communication in the digital era to optimize the use of platforms such as TikTok in political contexts.